Evolução filogenética e de traços do gênero Micrurus (Wagler, 1824) - Estrela, Matheus da Nóbrega (2020)
This work aimed to understand better how the phylogenetic evolution of the genus Micrurus occurred within the american continent, answering questions such as when the genus originated, where it was the center of dispersion, and which path the species took until its current distribution. To do this, we first constructed a phylogeny based on the NADH sub-unit 4 gene, which revealed the group's emergence still during the Miocene, before what other related works say. The tricolor monads and triads color pattern species formed two monophyletic groups. By the divergence times presented by our phylogeny, we corroborate with the current hypothesis that the ancestral population of Micrurus entered South America through an arch of islands that connected North and South America during the Miocene, and that the genus had a South American origin. We also suggest that the creation of Central America with the closing of the Panama’s Isthmus; the uplift of the Andes Mountain Range; the closure of the Acre System forming the Amazon River; and the rise of the Brazilian Central Plateau were key factors for the evolution of Micrurus. Furthermore, our data indicate that the center of dispersion of the genus was in the north of South America, from where an ancestral population of the monad group migrated towards the south, colonizing the east coast of the continent and the Amazon Forest - after the closure of the System Acre - and a second population migrated towards Central and North America - after the closing of the Panama’s Isthmus. The triad group dispersed towards the south, colonizing from dry areas in the Caatinga and Brazilian Cerrado, to wet areas in the Amazon. The divergence of South American species was greatly influenced by the Andes uplift, which was probably responsible for vicariance events, separating species on the cis- and trans-Andes sides. In addition, we tested the hypothesis that the so-called aposematic coloration of the snakes of the genus Micrurus is co-evolving with the toxicity of their venom. And, this time, two phylogenies were built for each of the two main toxins from Micrurus' venom, PLA2 and 3FTx, to be compared with the NADH phylogeny that shows us how the group's evolutionary history occurred. Thus, when analyzing the groups formed in the NADH phylogeny we suggested that the color pattern of these snakes is a characteristic linked to the phylogenetic history of the group, and not so much to environmental factors. Likewise, the groups formed in the toxin trees made us suggest that the composition of the venom of these snakes also follows the evolutionary history of the group, rather than environmental factors. With these results, we suggest that the genes responsible for the expression of the coloration of coral snakes are closely linked to the genes encoding the toxins that make up their venom, and thus, these two characteristics may actually be in coevolution, and the coloration does, in fact, have an aposematic function in these snakes.